Guide for DIKSHA Implementation in Schools - Anchal Sharma (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
In India, various ICT tools and platforms are providing an opportunity for educators to share and optimize resources among each other and helping to learn. The government has launched various initiatives like 'Digital India' campaign to take advantage of the larger scale penetration of the Internet to reach every corner of the country. DIKSHA platform is a part of one such initiative by the MHRD, envisioned as One - Nation - One digital platform serving as a digital platform for the teachers. The platform aims to create a repository of resources for educators and build a strong community. From its inception, DIKSHA has evolved and updated with various features and tools to make the platform more efficient. The document will guide the users to navigate through the platform and understand the prerequisites for the implementation of the DIKSHA platform in schools. The document will be useful for a diverse set of stakeholders, including teachers, school heads, administrators, parents, and students, for smooth implementation of DIKSHA platform.
Keywords: 330